The Parties of a Bill of Exchange and the Necessity of Drawee (Assignee)’s Consent; Preparation of the General Theory of Cession of Debt and Novation of Debt in Shīʿa Jurisprudence by a Comparative Study in Iranian and French Law - Seyyed Hossein Safaii; Mohammad Hadi Javaherkalam (آموزه‌‌های فقه مدني)
Acomparative study in Iranian and French law has been investigated and reviewed in this article around the contract of assignment and the necessity of drawee (Arabic: مُحال ‌عَلَیه, assignee)’s consent in order to use the results of the discussion to prepare the general theory of cession of debt and seeking in Shīʿa jurisprudence. The question is, who are the parties to the contract of a bill of exchange and whether it is necessary to obtain the consent of the drawee for the conclusion or effect of the contract of the bill of exchange? Moreover, is it possible to deduce the institution of transfer of religion and cession of debt and novation of debt in a direct manner from this discussion in Shīʿa jurisprudence and civil law and is it possible to analyze the second and third paragraphs of Article 292 Civil Code based on it? We came to the conclusion by a descriptive-analytical research method and by studying jurisprudence texts and legal doctrine that the stronger opinion in Shīʿa jurisprudence and Iranian law is that the consent of drawee (assignee) is necessary for the occurrence of the bill of exchange and he/she is considered as a party to the contract and the death or incapacity (Arabic: حَجْر) of each of drawer (Arabic: مُحیل, assignor) or creditor (Arabic: مُحْتال, beneficiary of a draft) or drawee (Arabic: مُحال ‌عَلَیه, assignee) between offer (Arabic: إیجاب) and the last acceptance (Arabic: قَبول) causes the extinction of the validity of the agreement (Arabic: تَراضی, mutual consent). In addition, among the rules of bill of exchange and issues which are discussed in jurisprudential texts and civil law can accept the validity of cession of debt and novation directly in Shīʿa jurisprudence and Iranian law. Thus, contrary to what was common in Roman law and old French law, the “active deb” (claim), like tangible assets can be transferred to another even without the consent of the debtor. Also, unlike Roman Law and Old and New French Law (before the 2016 and 2018 reforms), “debt” is separate from obligor and the debtor can transfer the debt to a third party with creditor’s consent by materializing this constructive being which has long been accepted in Shīʿa jurisprudence and finally recognized it after centuries of disagreement and doubt in 2016.